Monte Carlo Evaluation of the Europa Clipper TID Margin Based on the Variability of the Jovian Radiation Environment With Application for Mission Design. Issue 2 (18th February 2020) - Andersen, A.; Kim, W.; McClure, S.; Jun, I.
Abstract: The Europa Clipper mission will repeatedly pass in and out of the Jovian radiation belts as it explores the icy moon. In order to evaluate the effectiveness of any safety margins for total ionizing dose (TID) ratings on Europa Clipper spacecraft components, the variability of the expected radiation environment must be considered. This study outlines a Monte Carlo calculation of the cumulative probability that the TID will deviate from the nominal value of 150 krad (Si) based on the lognormal distributions of electron fluxes observed in the Jupiter environment by the Galileo Energetic Particle Detector instrument. Our model shows that parts hardened to 300 krad (Si) for a radiation design factor of 2 are expected to withstand the measured variations of the Jupiter radiation environment with margin. This result can be scaled to apply to all parts and materials with different TID levels for the Europa Clipper mission. Key Points: We describe a Monte Carlo model of the variability of the Jovian radiation environment based on Galileo energetic particle detector data We show that there is a negligible probability of TID exceeding a radiation design factor of two for the mission trajectory Our Monte Carlo calculation is insensitive to possible trends in the Jovian radiation environment observed in the Galileo EPD data